HUBUNGAN DUKUNGAN KELUARGA DENGAN KUALITAS HIDUP PASIEN GAGAL GINJAL KRONIK YANG MENJALANI TERAPI HEMODIALISIS DI RSUD ARIFIN ACHMAD PEKANBARU - Utami, Gamya Tri; ', Zurmeli '; ', Bay hakki (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract The purpose of study was to identify the correlation between the family support and quality ofÂ life of patients with chronic renal failure undergoing hemodialysis therapy at Arifin Achmad general hospital Pekanbaru. This study was description correlation with cross sectional approach. Sampling technique in this study was total sampling with 105 respondents. Instruments used were questionnaires which were tested the validity and reliability. Data analysis used univariate and bivariate analysis. The result showed that pvalue = 0.002, it could be concluded that there was a relationship between family support and quality of life of CRF patients undergoing hemodialysis therapy at Arifin Achmad general hospital Pekanbaru. Families who have family member undergoing hemodialysis therapy are expectedÂ to always give both moral and material support, so that the quality of life of patients undergoing hemodialysis CRF can be maintained. Keywords : Family Support, CRF, Hemodialysis, Quality Of Life